Comparing the Cognitive Functioning Effects of Aerobic and Pilates Exercises for Inactive Young Adults: A Randomized Controlled Trial. Issue 1 (February 2022) - Kaya, Begum Kara; Alpozgen, Ayse Zengin
Aerobic exercises (AE) have been found to have short-term positive effects on certain aspects of cognitive functioning. Pilates exercises (PE) may have similar benefits. In this randomized controlled study, we compared the effectiveness of PE and AE on participants' cognitive functions. We randomly assigned 52 physically inactive young adult volunteers into either a PE group ( M age = 20.85, SD = 2.11 years; 18 females and 8 males) or an AE group ( M age = 19.88, SD = 0.91 years; 18 females and 8 males). In both groups, participants engaged in a moderately intense exercise program three days a week for four weeks. We tested participants on cognitive measures of selective attention and inhibitory control (Stroop test), verbal fluency (verbal fluency tests (letter and category); VFTs), and speed of movement (Nelson's Speed of Movement Test; NSMT). There were no group differences on the Stroop and the VFTs ( p >0.05). However, there was a significant pre- to post-exercise difference for participants in both groups with a medium-large effect size (ES) on Stroop sections 1, 3, 4, and 5, respectively (PE: p < 0.001, ES = 0.58, p = 0.001, ES = 0.54, p < 0.001, ES = 0.88, p = 0.001, ES = 0.60; AE: p < 0.001, ES = 0.70, p < 0.001, ES = 0.89, p < 0.001, ES = 0.86, p = 0.006, ES = 0.65). There was a large effect size pre- to post-exercise detected for VFT sections labeled letter (PE: p < 0.001, ES = 1.45; AE: p < 0.001, ES = 1.11), and category (PE: p < 0.001, ES = 1.11; AE: p < 0.001, ES = 0.83), and there was a large ES for NSMT in the PE group ( p < 0.001, ES = 1.07). Both PE and AE may lead to short-term improvements in selective attention, verbal fluency, and executive control in inactive young adults, and PE may benefit speed of movement.